ACCOUNTING FOR SYSTEM-WIDE REGULARITIES IN THE MODELING OF COMPLEX SYSTEMS BY MEANS OF THE SYSTEM-OBJECT APPROACH - Sergey Igorevich Matorin; Sergey Pavlovich Belov; Alexander Gennadievich Zhikharev (Наука. Инновации. Технологии)
Introduction: the relevance of the study is due to the lack of justification of system-wide laws and principles from a unified position within the framework of the traditional set theory of systems, on the basis of which existing methodologies of analysis and synthesis of systems are constructed. Research methods: the results obtained within the framework of this article are a continuation of the research work on the creation of a formalized theory of simulation modeling of processes and systems. Earlier, the authors developed formal bases for the calculation of functional objects using the Abad-Kardeli calculus. There were introduced such terms as: stream and node objects. The formal foundations of the states of flow and core objects, as well as their interrelations, are determined. In addition to implementing the procedures for synthesis and analysis of systems, the results obtained opened the prospects for formalized accounting in system-object models of system-wide principles and regularities. In work with the above-mentioned calculation of Abadi-Kardeli objects, the deinition of the system within the system-object approach "Node-Function-Object" is clarified, and a formalization of the concepts "system-forming factor" and "system adaptation" is proposed. Results of the study and their discussion: the presented formalisms were used to take into account system-wide regularities in the construction of graphoanalytical models of organizational-business and industrial-technological processes in terms of "Node-Function-Object". The described approach makes it possible to distribute known system-wide regularities into three groups: related to the structural properties of systems related to their functional properties and to substantial properties, which justi-ies the hierarchical dependence between them. Formally, it is shown that the principle of organizational continuity is fulilled only if the principle of mono-centrism is observed, understood broadly. The possibilities of system-object, system-structural, object-oriented approaches and BPMN notation to consider system-wide regularities in graphoanalytical models are investigated. Conclusions: the authors concluded that the system-object approach "Node-Function-Object" allows to take into account from one position the existing system-wide laws and principles to a greater extent than other approaches. That, in turn, opens up new prospects for simulation of processes and systems, namely: the processes of adaptation and evolution of systems.